The RhoA dependent anti-metastatic function of RKIP in breast cancer - Gardiyawasam Kalpana (Nature Portfolio, 2021)
Abstract Raf-1 kinase inhibitor protein was initially discovered as a physiological kinase inhibitor of the MAPK signaling pathway and was later shown to suppress cancer cell invasion and metastasis. Yet, the molecular mechanism through which RKIP executes its effects is not completely defined. RhoA has both a pro- and anti-metastatic cell-context dependent functions. Given that Rho GTPases primarily function on actin cytoskeleton dynamics and cell movement regulation, it is possible that one way RKIP hinders cancer cell invasion/metastasis is by targeting these proteins. Here we show that RKIP inhibits cancer cell invasion and metastasis by stimulating RhoA anti-tumorigenic functions. Mechanistically, RKIP activates RhoA in an Erk2 and GEF-H1 dependent manner to enhance E-cadherin membrane localization and inhibit CCL5 expression.